The clinical research into the application of multifunctional airbag abdominal pressure belt in midwifery and in the prevention of postpartum hemorrhage. (2nd January 2018) - Zhao, Shaofei; Wen, Jiying; Niu, Jianmin; Xia, Jiaohong; Zhou, Liping; Zou, Wenxia
ABSTRACT: Objective: Explore the effect of the multifunctional airbag abdominal pressure belt on midwifery and on the prevention of postpartum hemorrhage. Methods: Select 363 natural delivery cases of hospitalized primiparae and divide them randomly into two groups. In the observation group, 182 primiparae used the multifunctional airbag abdominal pressure belt during the second and third stages of labor, whereas the control group of 181 did not use the belt. Delivery outcomes of the primiparae and their fetus were then observed. Results: The average duration for the second stage of labor, from head emergence to delivery, placenta delivery and postpartum hemorrhage were all shorter in the observation group ( p < 0.01). There was no statistical difference in episiotomy rate, maternal signs 2 h postpartum, neonatal Apgar score and neonatal cord blood gas analysis ( p > 0.05). No statistical difference was found in primipara signs and no fetal heart rate change of the primiparae under different internal pressures of the belt during the second stage of labor in the observation group ( p > 0.05). Conclusion: By closely monitoring and appropriately adjusting the internal pressure of the belt, the multifunctional airbag abdominal pressure belt can speed up the second and third stages of labor, prevent postpartum hemorrhage and promote natural delivery.